Performance analysis of power control for minimizing interference on LTE-A Femtocell: article / Mohammad Nasrul Hafiz Shah Room - Shah Room, Mohammad Nasrul Hafiz (2014)
The increases of user network today may lead to the capacity degradation and problems hence become the major issue that must be concerned in Mobile Communication Networks. Even though the Long Term Evolution - Advanced (LTE A) well known as the 4th generation of the Mobile Cellular Communication Network, it could not longer to solve the problems regarding capacity of the cell network. In fact that networking is an important thing to the world today. Femtocell deployment is considered to be the most efficient way to improve the capacity of cell and performance of mobile service especially in high traffic user at urban area. However, the radio signal interferences were occurs in Macrocell that cause the capacity degradation in LTE-A Femtocell. Therefore, minimizing the interference in LTE-A Femtocell power control technology is necessary. The objective of the research is to analyse power control for minimizing the interferences applying on LTE-A Femtocell. The method is by adapting the LTE-A Fractional Power Control (FPC) scheme to the LTE-A environment and proposing new Open Loop Uplink Power Control (OLUPC) technique for LTE-A Femtocell. The program is based on MATLAB simulation. From the compared simulation results the stable Signal to Interference plus Noise Ratio (SINR) performance is recommended for the proposed scheme.